Assessing the Complementarities of Colombia’s Renewable Power Plants - Parra, Laura; Gómez, Sara; Montoya, Carolina; Henao, Felipe (Frontiers in Energy Research, 2020)
Comprehending the complementarities between a country’s renewable power plants can help strategically plan for the future of its power system. Furthermore, complementarity can reduce the system’s vulnerabilities and its dependency on a single energy source. The Colombian power system significantly depends on hydroelectricity, which meets approximately 65% of the country’s electricity demand, making it vulnerable to droughts, particularly those caused by the El Niño–Southern Oscillation. Using either gas or coal power plants during a drought to back up the power system is expensive and polluting. This paper assesses the complementarities of Colombia’s hydro, wind, and solar power plants, with the purpose of identifying the weaknesses and strengths of the system and suggest a way for redressal. Complementarity is assessed via Pearson’s correlation analysis and Beluco et al. (2019) complementarity dimensionless indexes. The results suggest that the Colombian power system lacks complementarity, but it can be enhanced by investing in solar and wind power plants.